Diversity and variability of biomolecules under material and environmental factors in Cymbopogon citratus L., traditional uses, antimicrobial properties, and recommendations for future research - Noura Jaouad; Ahmed Tazi; Faouzi Errachidi; Souad Maache; Belkheir Hammouti; Mustapha Taleb (Kuwait Journal of Science, 2025)
Studies conducted on Cymbopogon citratus L., or lemon grass, have identified several active compounds that promote a variety of biological functions. However, existing data demonstrates a significant variability in the quality and quantity of chemicals that impact their biological properties and medicinal uses of the plant. Therefore, this study summarizes existing data on the diversity and variability of bioactive compounds in extracts of Cymbopogon citratus, their traditional uses, and their antimicrobial properties. To achieve these goals, we used an electronic literature review using targeted keywords related to the study topics and research gathered from papers published between 1980 and 2024. Recorded data demonstrated a wide range of chemical compounds, including polyphenols, flavonoids, terpenes, etc. These chemicals were variable between extracts and essential oils depending on plant materials, growing conditions, and extraction methods. Due to their richness in chemicals, different parts and extracts of Cymbopogon citratus are used in traditional medicine to manage anticancer, antimicrobial, antidiarrheal, antiamoebic, antifilarial, antiseptic, antitussive, analgesic, anesthetic, and anti-inflammatory diseases. In terms of antimicrobial activities, extracts and essential oils, as well as their components, showed a significant inhibitory effect against bacteria, fungi, and viral agents. These inhibitory effects are related to the capacity of bioactive molecules to impact the cells and intracellular components of treated microorganisms. To confirm these early findings, more in vitro and in vivo research on the anticancer and antioxidant mechanisms revealed by lemongrass components is necessary. Equally, in silico studies are needed to clarify the action mechanism of chemical compounds contained in the extracts and essential oils of lemongrass.